Enhanced photocatalytic properties of band structure engineered Pd/TiO2 via sequential doping - Lee, Sang Yeon; Yoo, Il Han; Singh, Ranveer; Lee, Young Jae; Kalanur, Shankara S.; Seo, Hyungtak (Applied Surface Science, 2021)
Band structure engineering is an essential and promising approach for altering photocatalytic properties of TiO2 for enhanced H2 production and dye degradation reactions. Given this, we propose the fluorine incorporation strategy to the Pd decorated TiO2, via the sequential doping process, using hydrogen and fluorine exhibiting a record photocurrent of ∼2 mA cm−2 (at 1.23 V vs RHE under 1 sun condition), and enhanced rhodamine B degradation. The physicochemical origin of increased photocatalytic activity is ascribed to the effective fluorine doping into the TiO2 lattice via O-vacancies, and to the resulting modified band electronic structure that generates high energy carriers. Furthermore, an insight into the properties of sequential doped Pd loaded TiO2 nanorod (Pd/F:TiO2-x NR), under the scheme of F-Ti3+ gap, states that mediated photocatalysis is provided with Ti-F bonding. Importantly, nanoscale imaging is used to monitor the direct charge at the surface of doped TiO2, which revealed valuable insights for the enhanced photocatalytic activity of TiO2.
Keywords: Band structure engineering; Degradation reaction; Doping process; Dye degradation; H 2 production; Photocatalytic activities; Photocatalytic property; Photoelectrochemicals; Sequential doping; Water splitting; Fluorine; Photoelectrochemical; Sequential doping; Titanium dioxide; Water splitting